Web Blended Learning: Inovasi Model Pembelajaran Digital Menuju Efektivitas Belajar Online - Pradnyana, I Ketut Andika; Ketut Agustini; I Wayan Santyasa (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2025)
Blended Learning is an innovative instructional model that combines face-to-face methods and online learning by utilizing information and communication technology. This article analyzes 15 international journals discussing various Blended Learning models, including Face-to-Face Driver, Rotation, Flex, Online Lab, Self Blend, and Online Driver. The study was conducted through content analysis focusing on the scope of Blended Learning, concepts, research methodologies, data collection techniques, instruments, and data analysis used in the studies. The analysis results indicate that Blended Learning, as a hybrid approach between conventional and online learning, has a positive impact on students' learning outcomes. Moreover, the Blended Learning model offers flexibility and effectiveness capable of addressing the challenges of online education. This study recommends the development and implementation of adaptive Blended Learning models as innovative solutions to enhance the quality of online learning